Graphene paste for anticorrosive coating and method for preparing the same

CN122917634APending Publication Date: 2026-10-16INTEGRITAS PAINT (HUANGSHAN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611334316.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

直接加入涂料不仅无法发挥纳米增强效应,反而会形成应力集中点和微观缺陷,加速局部腐蚀

Benefits of technology

[0020]与现有技术相比,本发明的有益效果至少可以包括:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BUIBCPOWPUD0IPGAHJMHWVFKHPJBTHTOOYEF9B8B
    Figure BUIBCPOWPUD0IPGAHJMHWVFKHPJBTHTOOYEF9B8B
  • Figure ICYSOMBKLAXPRS8IAHMYC8SOB1O64ELAPGXMXGBI
    Figure ICYSOMBKLAXPRS8IAHMYC8SOB1O64ELAPGXMXGBI
Patent Text Reader

Abstract

The present application provides a graphene slurry for anticorrosive paint and a preparation method thereof. Based on the total weight of the graphene slurry, the graphene slurry comprises: 10wt% to 50wt% of epoxy resin; 6wt% to 16wt% of graphene; 0.3wt% to 2.5wt% of silsesquioxane; 1wt% to 12wt% of auxiliary agent; and the balance of solvent, the graphene comprises first graphene and second graphene, the first graphene is unmodified graphene, the second graphene is amino and sulfonic acid group-containing graphene, and the silsesquioxane comprises octaamino cage polysilsesquioxane. The storage stability of the graphene slurry is significantly improved, and the anticorrosive performance achieved by the paint comprising the same is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of anti-corrosion coatings technology, specifically to a graphene slurry for anti-corrosion coatings and its preparation method. More particularly, it relates to a graphene slurry for epoxy-based anti-corrosion coatings and its preparation method. Background Technology

[0002] Graphene is considered a revolutionary filler for next-generation heavy-duty anti-corrosion coatings due to its unique two-dimensional sheet structure and excellent physicochemical properties. Its anti-corrosion mechanism is mainly based on: (1) physical shielding, "maze effect", which prolongs the diffusion path of corrosive media; (2) conductivity, which can transmit cathodic protection current; and (3) mechanical reinforcement, which improves the density and adhesion of the coating.

[0003] However, the practical application of graphene in anti-corrosion coatings faces three major bottlenecks: First, it suffers from poor dispersion stability. Strong van der Waals forces and π-π stacking interactions exist between graphene sheets, making them highly susceptible to irreversible aggregation. Directly adding them to coatings not only fails to achieve the nano-reinforcement effect but also creates stress concentration points and microscopic defects, accelerating localized corrosion. Pre-preparing graphene into a dispersion slurry is a common industry practice, but existing graphene slurries generally suffer from poor storage stability, exhibiting significant stratification and sedimentation after 15-30 days at room temperature.

[0004] Second, the interfacial compatibility and bonding strength are insufficient. The intrinsic graphene surface is chemically inert, resulting in weak interfacial bonding with polar epoxy resin. This weak interfacial interaction leads to the formation of microcracks at the filler-resin interface when the coating is subjected to external forces or undergoes thermal cycling. These microcracks provide rapid penetration channels for corrosive media such as water, oxygen, and chloride ions, weakening the shielding effect of graphene.

[0005] Third, single modification strategies suffer from the contradiction of sacrificing some functional aspects. In existing technologies, while covalent modification (such as introducing carboxyl or amino groups) can improve the dispersibility and interfacial compatibility of graphene, it inevitably disrupts the spline structure of graphene. 2 Conjugated structures sacrifice conductivity and mechanical enhancement. While non-covalent modification (such as surfactant coating) can maintain structural integrity, its dispersion effect and long-term stability are limited. How to achieve a balance between dispersibility, interfacial bonding, and structural integrity has long been a technical challenge that the industry has not been able to solve.

[0006] Therefore, there is an urgent need to develop a graphene slurry product that can simultaneously solve the above problems and achieve a combination of high dispersion stability, strong interfacial bonding, and long-term corrosion resistance.

[0007] The information disclosed in this background section is only for enhancing the understanding of the background technology of the present invention, and therefore may include information that does not constitute prior art. Summary of the Invention

[0008] To address the aforementioned problems with existing graphene slurries used in anti-corrosion coatings, this invention provides a graphene slurry with improved storage stability and overall performance, as well as its preparation method.

[0009] However, the present invention is not limited to the above aspects, but can be extended in various ways without departing from the technical spirit of the present invention.

[0010] One aspect of the present invention provides a graphene slurry for use in anti-corrosion coatings, wherein, based on the total weight of the graphene slurry, the graphene slurry comprises: 10 wt% to 50 wt% epoxy resin; 6 wt% to 16 wt% graphene; 0.3 wt% to 2.5 wt% silsesquioxane; 1 wt% to 12 wt% additives; and the balance being a solvent, wherein the graphene comprises a first graphene and a second graphene, the first graphene being unmodified graphene, the second graphene being graphene containing amino and sulfonic acid groups, and the silsesquioxane comprising octaaminocage-type polysilsesquioxane.

[0011] In the embodiments, the second graphene is 2,5-diaminobenzenesulfonic acid-modified reduced graphene oxide.

[0012] In an embodiment, the average lateral dimension of the second graphene is greater than the average lateral dimension of the first graphene, the average number of layers of the second graphene is less than or equal to the average number of layers of the first graphene, the content of the second graphene in the graphene slurry is less than the content of the first graphene, and the content of the silsesquioxane in the graphene slurry is less than the content of the second graphene.

[0013] In an embodiment, in the graphene slurry, the weight ratio of the second graphene to the first graphene is 0.4:1 to 0.9:1, and the weight ratio of the silsesquioxane to the graphene is 0.05:1 to 0.1:1.

[0014] In the embodiments, the average lateral dimension of the second graphene is 9 μm to 15 μm, the average lateral dimension of the first graphene is 4 μm to 8 μm, the average number of layers of the second graphene is 1 to 5, and the average number of layers of the first graphene is 1 to 5.

[0015] In the embodiments, the sulfur atom content in the second graphene is 1.7at% to 2.1at%, the C / O atom ratio in the second graphene is greater than or equal to 15, and the amino content in the second graphene is 1.2at% to 1.6at.

[0016] In an embodiment, the graphene further includes a third graphene, which is a hydroxyl-containing graphene. The average lateral dimension of the third graphene is greater than the average lateral dimension of the first graphene and smaller than the average lateral dimension of the second graphene. In the graphene slurry, the content ratio of the third graphene to the second graphene is 0.2:1 to 0.5:1.

[0017] In the embodiments, the hydroxyl content in the third graphene is from 0.6 at% to 1.2 at%.

[0018] In an embodiment, based on the total weight of the graphene slurry, the graphene slurry comprises: 20 wt% to 40 wt% epoxy resin; 8 wt% to 12 wt% graphene; 0.3 wt% to 1.5 wt% silsesquioxane; 1 wt% to 8 wt% additives; and the balance being a solvent, wherein the solvent comprises one or more of xylene, n-butanol, toluene, ethylbenzene, N-methylpyrrolidone, N,N-dimethylformamide, acetone, tetrahydrofuran, ethanol, water, and ethyl acetate, wherein the additives comprise one or more of defoamers and dispersants.

[0019] Another aspect of the present invention provides a method for preparing a graphene slurry for anti-corrosion coatings, the method comprising the following steps: adding silsesquioxane and a first graphene to a solvent to obtain a first mixture; adding silsesquioxane and a second graphene to a solvent to obtain a second mixture; mixing the first mixture and the second mixture using a microchannel mixer to obtain a third mixture; and adding an epoxy resin and an additive to the third mixture.

[0020] Compared with the prior art, the beneficial effects of the present invention can include at least the following: 1. Physical barrier: The large-to-small size gradation of permeable graphene (first graphene) and amino-acid modified graphene (second graphene) constructs a dense labyrinthine physical shielding layer inside the coating, effectively extending the penetration path of corrosive media such as water, oxygen, and chloride ions.

[0021] 2. Chemical passivation and interface enhancement: The amino groups of second graphene (ASG) can form coordination bonds with oxides on the surface of metal substrates (such as iron and zinc), forming a stable passivation film in situ at the metal interface and inhibiting the cathode reaction of corrosion microcells. At the same time, in non-polar (or weakly polar) systems, the sulfonic acid groups (-SO3H) provide large-volume steric hindrance and form hydrogen bond-dipole interactions with the octaamino POSS, synergistically weakening the π-π stacking between graphene sheets, thereby significantly improving the dispersion stability of graphene.

[0022] 3. Crosslinking enhancement: The eight active amino functional groups of octaaminoPOSS can deeply participate in the curing reaction of epoxy resin, forming a three-dimensional network structure with high crosslinking density. This not only fills the free volume and micro-defects inside the coating, but also firmly anchors the graphene sheets in the resin network, achieving chemical bonding interface enhancement.

[0023] 4. Synergistic effect achieves a 1+1+1>3 improvement in corrosion resistance: The three mechanisms of physical shielding, chemical passivation and cross-linking enhancement work synergistically, making the composite coating perform far better than the coating modified by a single component in salt spray test, electrochemical impedance and other aspects.

[0024] 5. Excellent slurry storage stability: Through size gradation (large ASG and small unmodified graphene) and the steric hindrance effect of octaamino POSS, supplemented by the polar stabilizing effect of ASG's own sulfonic acid groups, the π-π stacking between graphene sheets is effectively weakened, achieving stable storage of the slurry for more than 6 months without delamination or gelation.

[0025] The effects of this invention are not limited to those mentioned herein, and those skilled in the art will clearly understand other effects from the description of the claims. Detailed Implementation

[0026] The present invention will be further described in detail below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. After reading the contents of this invention, those skilled in the art can make various alterations or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0027] In the specific embodiments of this invention, unless otherwise stated, all chemical raw materials used are conventional commercially available reagents. Various auxiliaries, fillers, catalysts, etc., involved can be obtained through commercial channels or prepared according to methods known in the art. The equipment used in this invention is all conventional equipment in the art; its model and specifications do not affect the implementation of the technical solution of this invention, and those skilled in the art can make reasonable selections according to actual production scale and process requirements.

[0028] For inventions involving chemical compositions, the content of each component in the specific embodiments is expressed in parts by weight, weight percentage, or molar ratio, and the specific expression method is determined according to the properties of the composition and the conventions of the relevant technical field. The selection of the content range of each component is based on its influence on the final material properties, and the technical effects of the present invention can be achieved within the scope disclosed in this invention. Those skilled in the art will understand that both the endpoint values ​​and intermediate values ​​of the content of each component can achieve the purpose of the present invention, and the specific values ​​can be adjusted according to actual needs.

[0029] In the preparation method of this invention, the operating temperature, time, pressure, pH value, stirring speed, and other process parameters of each process step are all within the conventional range in the art. Those skilled in the art can optimize and select within the above range according to the actual equipment conditions and raw material characteristics. It should be understood that the range of process parameters disclosed in this invention includes endpoint values ​​and any values ​​between endpoint values. These values ​​can all achieve the technical effects of this invention and are all within the protection scope of this invention.

[0030] The graphene slurry for preparing anti-corrosion coatings and its preparation method of the present invention will be described in detail below.

[0031] In the following description, the theoretical basis of graphene slurry and its preparation method according to some embodiments of the present invention may be involved. It is understood that these theoretical basis are only for the purpose of understanding the present invention and are not intended to limit the present invention in any way. That is, the effects of the graphene slurry and its preparation method of the present invention are not limited by these theoretical basis; that is, they may not be based on these theoretical basis, or they may be based on other theoretical basis besides these theoretical basis.

[0032] Graphene slurry As mentioned above, existing graphene predispersed slurries for anti-corrosion coatings suffer from problems such as poor dispersion stability of graphene, insufficient interfacial compatibility and bonding force between graphene and epoxy resin, and difficulty in comprehensively considering various performance aspects through improvement methods.

[0033] To address at least one of the aforementioned problems, the present invention first proposes a graphene slurry for use in anti-corrosion coatings. This graphene slurry comprises a solvent, an epoxy resin, graphene, silsesquioxane, and additives. The graphene comprises a first graphene and a second graphene, wherein the first graphene is unmodified graphene, and the second graphene is modified graphene containing amino and sulfonic acid groups.

[0034] In this article, for ease of description, unless otherwise specified, “graphene” may refer to native graphene (or intrinsic graphene or pure graphene) that is essentially free of heteroatoms and defects, graphene oxide, reduced graphene oxide, and any combination thereof.

[0035] This invention is the first to propose a ternary compound slurry system using unmodified graphene (first graphene), modified graphene containing amino and sulfonic acid groups (second graphene / ASG), and silsesquioxane (specifically, cage-type polysilsesquioxane), thereby constructing a multi-synergistic anti-corrosion functional system.

[0036] The components of the graphene slurry of the present invention will be described in detail below.

[0037] Second graphene The second graphene is a modified graphene containing amino and sulfonic acid groups. In embodiments, the second graphene may be modified intrinsic graphene, modified graphene oxide, or modified reduced graphene oxide. In a preferred embodiment of the invention, the second graphene may be a modified reduced graphene oxide containing amino and sulfonic acid groups.

[0038] Existing amino-modified graphene (such as ethylenediamine-modified and p-phenylenediamine-modified) only introduces a single amino functional group. Although the amino group can react with epoxy resin to provide interfacial bonding, this type of modified graphene still faces the problem of insufficient dispersion stability.

[0039] In contrast, the second graphene of the present invention is a modified graphene containing amino and sulfonic acid groups, which simultaneously possesses amino and sulfonic acid groups.

[0040] In the non-aqueous organic solvent system of this invention, although the sulfonic acid groups do not ionize, their strong polarity endows the modified graphene sheets with several key roles. First, the large volume of sulfonic acid groups forms effective physical steric hindrance between the sheets, directly suppressing the aggregation of graphene sheets caused by π-π stacking. Second, the sulfonic acid groups provide large-volume steric hindrance, while hydrogen bonding / dipole interactions are formed between sulfonic acid, amino groups, and octaamino POSS. POSS adsorbs and coats the graphene sheets, achieving steric stabilization and further enhancing the slurry's resistance to sedimentation during storage. Finally, after the coating cures, the strong polar interaction between the sulfonic acid groups and the resin matrix also provides additional bonding force at the filler-resin interface.

[0041] Amino groups can achieve both chemical passivation and interfacial anchoring. Amino groups possess lone pairs of electrons, enabling them to form coordination bonds with the metal substrate, generating a stable chemisorption layer or passivation film in situ at the metal interface. This passivation film not only blocks the cathodic reaction of the corrosion microcell but also allows for rapid passivation of the exposed metal surface even if the coating is partially damaged, inhibiting corrosion propagation. Furthermore, amino groups can undergo ring-opening addition reactions with the epoxy groups of epoxy resins, forming covalent bonds that chemically anchor the ASG sheets within the resin crosslinking network, significantly improving the bonding strength at the filler-resin interface.

[0042] Therefore, the second graphene of the present invention achieves the effect that a single functional group modification scheme cannot achieve by simultaneously containing amino and sulfonic acid groups.

[0043] In a preferred embodiment of the present invention, the second graphene may be 2,5-diaminobenzenesulfonic acid-modified reduced graphene oxide. The second graphene may be a commercially available product or may be prepared in-house.

[0044] First Graphene In addition to the second graphene, the present invention also includes a first graphene as an unmodified intrinsic graphene.

[0045] While ASG solved the dispersion and passivation problems through functional group grafting, covalent modification inevitably disrupted the spline properties of graphene. 2 Conjugated structure. Grafting of sulfonic acid groups and amino groups causes some carbon atoms to be converted from sp... 2 The hybridization shifts to sp³ hybridization, leading to a decrease in the conductivity of graphene. If ASG is used exclusively, the coating will lack efficient electron transport channels, which is extremely disadvantageous for systems that require the utilization of graphene's conductivity for cathodic protection.

[0046] Therefore, this invention constructs a complete conductive network and mechanically reinforcing framework by retaining a certain proportion of unmodified graphene (first graphene). The unmodified graphene has not undergone any covalent chemical modification, and its sp... 2 The conjugated carbon network remains intact and exhibits excellent intrinsic conductivity. Furthermore, through the specific selection of the sizes of the two graphene types, the fine sheets of the first graphene can intersect between the large ASG sheets, filling the micropores formed by the overlapping ASG sheets and constructing a continuous three-dimensional conductive pathway. Simultaneously, the complete aromatic π-plane of the first graphene can generate non-covalent interactions with the amino groups of the octaamino POSS (through hydrogen bonding or electrostatic interactions) or the benzene rings in the epoxy resin, further enhancing dispersion stability.

[0047] However, unmodified graphene has poor compatibility with solvents due to the lack of grafted functional groups and is prone to aggregation. Therefore, it needs to be compounded with ASG in a specific ratio.

[0048] Therefore, by combining the first and second graphene, the present invention not only improves the dispersion stability of the slurry and enhances the bonding strength between graphene and the metal surface and resin matrix, but also stably maintains the conductive network constructed by graphene.

[0049] Silsesquioxane In addition to the first and second graphenes mentioned above, the graphene slurry of the present invention also includes silsesquioxane. Silsesquioxane can disrupt the original π-π stacking forces between graphene sheets, thereby effectively preventing the agglomeration of graphene sheets.

[0050] In a preferred embodiment of the present invention, the silsesquioxane may be a cage-like polysilsesquioxane (POSS). In a preferred embodiment of the present invention, the silsesquioxane may be an octaaminoPOSS.

[0051] The amino groups grafted onto the ASG surface and the eight amino groups of the eight-amino POSS together constitute a high-density amino enrichment system. This high-density amino environment forms a more compact and complete passivation film at the metal interface, and its passivation effect is far superior to using ASG or POSS alone.

[0052] Furthermore, the amino groups on ASG react with epoxy resin to form chemical bonds, anchoring ASG within the resin network; the eight amino groups of the eight-amino group POSS act as multifunctional crosslinking sites, crosslinking multiple resin chains together. When ASG and POSS are present simultaneously, the ASG sheets are encapsulated and fixed by the crosslinking network of POSS, forming an inorganic-organic interpenetrating network (IPN) structure. This structure greatly restricts the migration and recombination of graphene sheets, enabling the coating to achieve a level of density and impermeability that cannot be achieved with a single component.

[0053] Furthermore, the combination of ASG and octaaminoPOSS achieves a synergistic improvement in dispersion stability. The sulfonic acid groups of ASG, through physical steric hindrance and surface polarity regulation, work synergistically with the steric hindrance stabilization mechanism provided by octaaminoPOSS, resulting in a dual steric hindrance stabilization effect within the same system. This dual stabilization mechanism ensures that the slurry remains non-stratified and non-sedimenting during storage for more than 6 months, exhibiting significantly better storage stability than systems relying on a single stabilization mechanism.

[0054] As described above, this invention achieves a three-in-one protective system of physical shielding, chemical passivation, and cross-linking enhancement in anti-corrosion coatings containing the slurry of this invention through the synergistic effect of unmodified graphene, ASG, and octaaminoPOSS. The combined effect of these three components makes the graphene slurry of this invention significantly superior to any single or binary component solution in terms of storage stability, coating adhesion, salt spray resistance, and electrochemical impedance.

[0055] Based on the above-mentioned inventive concept, the inventors have further studied and improved other configurations of the graphene slurry (e.g., the size and content of the first graphene, the second graphene, and silsesquioxane), thereby further improving the performance of the graphene slurry and the coatings prepared using it.

[0056] In a preferred embodiment of the invention, the average lateral dimension of the second graphene (ASG) is greater than the average lateral dimension of the first graphene (unmodified graphene). Hereinafter, "average lateral dimension" refers to the distance between the two furthest points on a graphene sheet when observed and measured in a direction perpendicular to the graphene sheet.

[0057] During coating curing, large-sized second graphene sheets, driven by surface tension, tend to spread parallel to the metal substrate. This large-area sheet spreading can form a long-range physical barrier in the coating, maximizing the diffusion path of corrosive media (water molecules, chloride ions, oxygen molecules, etc.). Simultaneously, since the second graphene is modified graphene containing amino and sulfonic acid groups, it has stronger adhesion to the metal substrate. In this case, using second graphene with a relatively large average lateral dimension can form a shielding layer with a larger coverage area in the dimension parallel to the metal substrate surface. Furthermore, since the modified groups are usually located at the edges of the graphene sheets, by using large-sized second graphene, a longer conductive path can be constructed using relatively fewer amino and sulfonic acid groups, thereby reducing the cost increase brought by modified graphene. On the other hand, by using larger-sized aminosulfonic acid-modified graphene, when the paint film formed by the coating has scratches, the flat, large-sized aminosulfonic acid-modified graphene can directly cover the damaged interface, and a large number of amino groups on the surface act simultaneously on the exposed metal, thus preventing the coating from failing when damaged.

[0058] However, the overlapping areas between large-sized graphene sheets inevitably contain gaps on the order of several micrometers. If only large-sized graphene is used, these gaps will become shortcuts for corrosive media to penetrate rapidly, severely weakening the shielding effect. In this case, small-sized first-stage graphene can precisely fill these gaps between the large-sized sheets, forming a secondary filling, so that there are almost no interconnected micropores inside the coating, achieving optimal shielding performance. This gradation effect of "large-sized sheets building the framework and small-sized sheets filling the pores" is something that single-sized graphene cannot achieve.

[0059] In a preferred embodiment of the invention, the average number of layers of the second graphene is less than or equal to the average number of layers of the first graphene. ASG with fewer layers exhibits better flexibility, a larger specific surface area, and is more easily bonded to metal substrates to form a continuous passivation film; unmodified graphene with slightly more layers provides better stress transfer and mechanical reinforcement, and the two complement each other.

[0060] In a preferred embodiment of the present invention, the content of the second graphene is less than the content of the first graphene. The content of the aminosulfonic acid-modified graphene is set to be relatively low because, firstly, its large-size, low-layer structure allows for bonding to the metal substrate, building a conductive network, and forming a continuous barrier film with a relatively small content. Secondly, if the content of large-size aminosulfonic acid-modified graphene exceeds the content of small-size unmodified graphene, the conductive pathways in the coating will primarily consist of ASG with numerous defects. In this case, the unmodified graphene (retaining complete sp...) 2The content of the graphene slurry is relatively insufficient, failing to fill the defects and form a continuous low-resistance channel. This results in a significant increase in coating resistivity, which reduces the charge dissipation capacity of coatings containing this graphene slurry, increasing the risk of galvanic corrosion.

[0061] Therefore, in this invention, the content of the second graphene (ASG) is less than the content of the first graphene (unmodified). This is because the large-size sheets of ASG provide efficient long-range overlap, and a small amount can perform passivation and dispersion functions. However, excessive ASG will lead to a decrease in the conductivity of the system, and the sulfonic acid group is a hydrophilic group, so an excessive amount may affect the water resistance of the coating.

[0062] In a preferred embodiment of the present invention, the content of silsesquioxane is less than the content of the second graphene. The mechanism of action of octaamino POSS is to intercalate between graphene sheets through the steric hindrance effect of its cage-like structure and the polar effect of its surface amino groups, thereby weakening the π-π stacking forces between the sheets and preventing aggregation. If the content of silsesquioxane is too high, not only will multilayer adsorption be formed on the graphene surface, but independent POSS aggregates may also form. In addition, since the siloxane framework of POSS itself is an insulator, excessive POSS will affect the conductive pathways between graphene sheets, resulting in a significant increase in coating resistivity, which is detrimental to the anti-corrosion mechanism utilizing the conductivity of graphene.

[0063] As described above, the present invention sets the size, thickness, and content of the unmodified first graphene and the aminosulfonic acid-modified second graphene, as well as the content of silsesquioxane, as described above, thereby further optimizing and improving the achieved effect.

[0064] Furthermore, based on the above improvements, the inventors studied the specific dimensions, number of layers, and content of the first and second graphene.

[0065] In a preferred embodiment of the present invention, the average lateral dimension of the second graphene is 9 μm-12 μm, and the average lateral dimension of the first graphene is 4 μm-8 μm. Within the above range, the effects described above can be better achieved.

[0066] For example, if the average lateral dimension of the second graphene is greater than 12 μm, the sheet area is too large, making it prone to wrinkles, folds, or buckling deformation in the coating, resulting in structural defects. Large sheets are also more likely to settle in the slurry, and when they exceed the coating thickness, they may puncture the coating surface, compromising coating integrity. If the average lateral dimension of the second graphene is less than 9 μm, it loses its function as a large-scale, long-range framework. The size difference with the first graphene is reduced, failing to form effective large-to-small gradation filling, leaving a large number of unfilled through gaps in the coating, significantly diminishing the labyrinth effect. If the average lateral dimension of the first graphene is less than 4 μm, its specific surface area is too large, resulting in a severe tendency to aggregate and making uniform dispersion difficult; furthermore, its small size is insufficient to effectively fill the gaps, which can be several micrometers wide, between large sheets. If the average lateral dimension of the first graphene is greater than 8 μm, it loses its micropore-filling function. The insufficient scale difference with the large sheets prevents complementary stacking and fails to seal micro-defects. Of course, the aforementioned size range is only a preferred embodiment of the present invention, and its theoretical description is only an explanation of the preferred solution, and does not constitute a limitation on the scope of protection of the present invention.

[0067] Furthermore, in a preferred embodiment of the present invention, the aspect ratio of the second graphene is 1 to 1.5. Here, "aspect ratio" refers to the ratio of the length to the width of a graphene sheet when observed and measured in a direction perpendicular to the graphene sheet. Here, "length" refers to the distance between the two farthest points on the graphene sheet when observed and measured in a direction perpendicular to the graphene sheet (i.e., the length of the major axis), i.e., the "average lateral dimension" mentioned above. "Width" refers to the distance between two points connected by an axis perpendicular to the major axis when observed and measured in a direction perpendicular to the graphene sheet. Therefore, the "aspect ratio" in this document can also be referred to as the "intra-sheet major axis-minor axis ratio".

[0068] Because the aspect ratio of the second graphene is 1 to 1.5, its shape is closer to that of a circle or square. Due to this shape, the second graphene is more likely to align approximately parallel to the coating surface after curing, allowing for greater coverage of the substrate and thus better corrosion resistance. Furthermore, since sulfamic acid groups are mostly concentrated at the edges of the graphene sheets, the second graphene with the aforementioned aspect ratio can contain more sulfamic acid groups per sheet, forming more bonding sites with the metal substrate and significantly improving the efficiency of the conductive network. Moreover, due to its near-circular or square shape, when the coating is scratched or damaged, the second graphene covering the interface can cover a large area of ​​the exposed substrate, quickly forming a metal passivation film and inhibiting lateral corrosion propagation. On the other hand, the second graphene with the aforementioned aspect ratio or shape is more likely to form multi-point π-π conjugated adsorption with the octaaminoPOSS described below, resulting in better dispersibility.

[0069] In a preferred embodiment of the invention, the aspect ratio of the first graphene is 5 or greater, thus its shape is closer to that of a strip. Due to this shape, the first graphene is easier to construct into a continuous, long-range conductive network. Compared to graphene sheets with low aspect ratios, the strip-shaped graphene has a lower tunneling resistance, resulting in a significant decrease in the sheet resistance of the coating with the same amount of graphene added. Furthermore, in the coating, the strip-shaped first graphene is interspersed linearly within the gaps of the coating film, avoiding large-area coverage of the film surface. This leaves the large-area lateral shielding and passivation functions to the second graphene with a low aspect ratio, achieving a separation of conductive and shielding functions.

[0070] In a preferred embodiment of the present invention, the aspect ratio of the second graphene can be 1 to 1.45, 1 to 1.4, 1 to 1.35, 1 to 1.3, 1 to 1.25, 1 to 1.2, 1 to 1.15, 1 to 1.1; 1.05 to 1.5, 1.05 to 1.4, 1.05 to 1.3, 1.05 to 1.2, 1.05 to 1.1; 1.1 to 1.5, 1.1 to 1.4, 1.1 to 1.3, 1.1 to 1.2; 1.2 to 1.5, 1.2 to 1.45, 1.2 to 1.4, 1.2 to 1.35, 1.2 to 1.3, 1.2 to 1.25. In a preferred embodiment of the present invention, the aspect ratio of the first graphene can be 5 to 15, 5 to 14, 5 to 13, 5 to 12, 5 to 11, 5 to 10; 6 to 15, 6 to 14, 6 to 13, 6 to 12, 6 to 11, 6 to 10; 7 to 15, 7 to 14, 7 to 13, 7 to 12, 7 to 11, 7 to 10; 8 to 15, 8 to 14, 8 to 13, 8 to 12, 8 to 11, 8 to 10. Within the above ranges, the effects described above can be better achieved.

[0071] In a preferred embodiment of the present invention, the second graphene has an average number of 1-5 layers, and the first graphene has an average number of 1-5 layers. Within the above range, the effects described above can be better achieved.

[0072] For example, if the number of graphene layers increases (e.g., more than 5 layers), its structure becomes thicker, its rigidity increases, its flexibility decreases, and its specific surface area decreases significantly, making it unable to form a dense overlapping coverage in the coating; its barrier properties are close to those of ordinary graphite powder, and it loses the specific performance advantages of graphene nanofillers. Furthermore, if the number of layers in aminosulfonic acid-modified graphene exceeds 5, the aminosulfonic acid groups at the edges of the relatively large number of graphene sheets cannot be effectively bonded to the metal substrate, resulting in a waste of aminosulfonic acid groups. Of course, the aforementioned range of layer numbers is only a preferred embodiment of the present invention, and its theoretical description is only an explanation of the preferred solution, and does not constitute a limitation on the scope of protection of the present invention.

[0073] In a preferred embodiment of the present invention, the weight ratio of the second graphene to the first graphene is 0.4:1 to 0.9:1. Within this range, the effects described above can be better achieved.

[0074] For example, if the weight ratio of the second graphene to the first graphene is less than 0.4:1, the proportion of aminosulfonic acid-modified graphene is too small. The system lacks sufficient sulfonic acid groups to provide dispersion stabilization and sufficient amino groups to provide metal passivation, resulting in unsatisfactory slurry storage stability and coating interfacial adhesion. If the weight ratio of the second graphene to the first graphene is greater than 0.9:1, the ASG content is too high. The conductive framework effect of the unmodified graphene in the system is weakened, the coating resistivity increases, and the excessive sulfonic acid groups in the ASG are hydrophilic groups, which may increase the water absorption rate of the coating, thus negatively impacting long-term water resistance.

[0075] In a preferred embodiment of the present invention, the weight ratio of silsesquioxane to graphene is 0.05:1 to 0.1:1. If the POSS / graphene ratio is less than 0.05:1, the number of POSS molecules is insufficient to effectively intercalate all graphene sheets, and some graphene will still agglomerate, resulting in increased slurry fineness and insufficient storage stability. If the POSS / graphene ratio is greater than 0.1:1, there is an excess of POSS molecules, which will not only form multilayer adsorption on the graphene surface but may also form independent POSS aggregates. Moreover, excessive POSS is detrimental to the corrosion protection mechanism utilizing the conductivity of graphene. Through the inventors' research, the range of 0.05:1 to 0.1:1 is an optimized ratio that controls the negative impact of POSS on the conductivity of the coating within an acceptable range while ensuring sufficient intercalation and dispersion. Within the above range, the effects described above can be better achieved. For example, the weight ratio of octaaminoPOSS to second graphene can be 0.1:1 to 0.15:1.

[0076] In a preferred embodiment of the present invention, the sulfur atom content in the second graphene is 1.7 at% to 2.1 at%.

[0077] The sulfur atom content reflects the grafting density of sulfonic acid groups on ASG. The grafting density of sulfonic acid groups directly determines the dispersion stability of ASG in the non-aqueous organic solvent system of this invention and its compatibility in the epoxy resin matrix. If the sulfur content is less than 1.7 at%, the sulfonic acid group grafting density is insufficient, the steric hindrance effect between ASG sheets is not sufficient, and it is difficult to effectively suppress π-π stacking and aggregation between sheets, making the slurry prone to stratification or sedimentation. If the sulfur content is greater than 2.1 at%, the excessive sulfonic acid groups form a dense polar layer on the surface of the ASG sheets. Although this is beneficial for short-term dispersion, it may increase the polarity and hygroscopic tendency of the coating after curing, thereby reducing the water resistance and long-term impermeability of the paint film. Simultaneously, excessive sulfonic acid groups mean more covalent bond modification sites, which affects the sp... 2 The conjugated structure causes greater damage, leading to a more significant decrease in its intrinsic conductivity and mechanical enhancement effect. 1.7at%-2.1at% is the optimal range for minimizing the negative impact of polar groups on the coating's water resistance and conductivity while ensuring good ASG dispersion in this system.

[0078] In a preferred embodiment of the present invention, the amino content in the second graphene is 1.2 at% to 1.6 at%.

[0079] The amino content determines the passivation ability of ASG to the metal substrate and the degree of reaction with epoxy resin. If the amino content is below 1.2 at%, the passivation effect of ASG on the metal is insufficient, and the improvement of interfacial adhesion is limited. If the amino content is above 1.6 at%, it means that the grafting density is too high, which will further damage the graphene structure on the one hand, and on the other hand, excessive amino groups may react with CO2 in the air during slurry storage to form carbamates, affecting the stability of the slurry. 1.2 at%-1.6 at% is the preferred range that balances passivation effect and storage stability.

[0080] In a preferred embodiment of the present invention, the C / O atomic ratio in the second graphene is greater than or equal to 15.

[0081] A higher C / O ratio indicates fewer oxygen-containing functional groups in graphene. 2 The more complete the conjugated structure, the better the intrinsic conductivity. This invention limits the C / O ratio of ASG to ≥15, meaning that ASG itself is mildly oxidized graphene, and its conjugated structure is preserved to the maximum extent. If the C / O ratio is below 15, it indicates that the degree of oxidation is too high, and the conductivity of graphene decreases significantly, which is not conducive to constructing a highly efficient conductive network. In this invention, ASG is amino and sulfonic acid-modified reduced graphene oxide; therefore, it has fewer oxygen-containing functional groups.

[0082] In a preferred embodiment of the invention, the graphene further includes a third graphene, which is a hydroxyl-containing graphene. For example, the third graphene may be or include reduced graphene oxide containing trace amounts of hydroxyl groups.

[0083] The polarity of hydroxyl groups is weaker than that of sulfonic acid groups, but stronger than that of the intrinsic hydrophobic surface of graphene. The introduction of an appropriate amount of hydroxyl groups gives the third graphene both weak polarity and a complete π-conjugated plane. Its weak polarity allows it to form hydrogen bonds with the polar groups of epoxy resins and weak interactions with the amino groups of octaamino POSS; the complete π-plane allows it to form π-π stacks with ASG and unmodified graphene. Therefore, the third graphene acts as a molecular bridge, connecting the components in the system more tightly, further reducing stratification and precipitation during slurry storage.

[0084] In a preferred embodiment of the present invention, the average lateral dimension of the third graphene is greater than the average lateral dimension of the first graphene and less than the average lateral dimension of the second graphene.

[0085] The size of the third graphene is limited to between that of the first and second graphene, thus forming a complete three-level gradation of "large (ASG) - medium (third graphene) - small (unmodified graphene)" in the ternary system, maximizing the density of the coating.

[0086] In a preferred embodiment of the present invention, the content ratio of third graphene to second graphene in the graphene slurry is 0.2:1 to 0.5:1.

[0087] If the content of the third graphene is too low, its auxiliary dispersion and gradation filling effects will be insignificant; if the content of the third graphene is too high, there will be too many hydroxyl-containing components in the system, which may increase the hydrophilicity and water absorption of the coating, and have an adverse effect on the long-term anti-corrosion performance.

[0088] In a preferred embodiment of the present invention, the hydroxyl content in the third graphene is 0.6 at% to 1.2 at%. Within this range, the total amount of hydroxyl groups in the third graphene is relatively low, and it will not significantly damage the spline structure of the graphene. 2 The conjugated network means that it does not significantly reduce the conductivity of the coating. If the hydroxyl content in the third graphene is too low (e.g., below 0.6 at%), the third graphene is essentially non-polar, making it difficult to form weak hydrogen bonds with epoxy resins and octaaminoPOSS.

[0089] In embodiments of the present invention, the graphene slurry may include: 10 wt% to 50 wt% epoxy resin, 6 wt% to 16 wt% graphene, 0.3 wt% to 2.5 wt% silsesquioxane, 1 wt% to 12 wt% additives, and the balance being solvent. Within the above range, the effects described above can be better achieved.

[0090] In a preferred embodiment of the present invention, the graphene slurry may include: 20 wt% to 40 wt% epoxy resin; 8 wt% to 14 wt% graphene; 0.3 wt% to 1.5 wt% silsesquioxane; 1 wt% to 8 wt% additives; and the balance being solvent. Within the above range, the effects described above can be better achieved.

[0091] In a preferred embodiment of the present invention, the graphene slurry may include: 25wt%-35wt% epoxy resin; 10wt%-12wt% graphene; 0.5wt%-1.0wt% silsesquioxane; 1wt%-6wt% additives; and the balance being solvent. Within the above range, the effects described above can be better achieved.

[0092] Solvents may include one or more of xylene, n-butanol, toluene, ethylbenzene, N-methylpyrrolidone, N,N-dimethylformamide, acetone, tetrahydrofuran, ethanol, water, and ethyl acetate. Additives may include, but are not limited to, one or more of defoamers and dispersants. Additives may also include one or more of antioxidants, coupling agents, leveling agents, thixotropic agents, etc.

[0093] Methods for preparing graphene slurry The present invention also provides a method for preparing a graphene slurry for use in anti-corrosion coatings as described above. The method includes the following steps: Step S100: adding silsesquioxane and first graphene to a solvent to obtain a first mixture; Step S200: adding silsesquioxane and second graphene to a solvent to obtain a second mixture; Step S300: mixing the first mixture and the second mixture using a microchannel mixer to obtain a third mixture; and Step S400: adding epoxy resin and additives to the third mixture.

[0094] In step S100, silsesquioxane can be added to the solvent first and stirred at 800-1200 r / min for 15-60 min. Then, the first graphene is added in batches (e.g., 2 to 5 batches). After all the graphene has been added, the rotation speed is increased to 1500-3000 r / min and dispersed at high speed for 30-120 min to obtain the first mixture.

[0095] In step S200, silsesquioxane can be added to the solvent first and stirred at 800-1200 r / min for 15-60 min. Then, the second graphene is added in batches (e.g., 2 to 5 batches). After all the graphene has been added, the rotation speed is increased to 1500-3000 r / min and dispersed at high speed for 30-120 min to obtain the second mixture.

[0096] In step S300, the first and second mixtures are fed to the two inlets of the microchannel mixer through independent feed lines, and mixed within the mixer. The feed flow rate ratio of the first and second mixtures is determined based on a preset ratio of the first and second graphene. The operating pressure of the microchannel mixer is 5-50 bar, the operating temperature is 10-60°C, and the residence time of the two liquids within the microchannel is 0.1-10 seconds. Within the confined space of the microchannel, the two liquids are divided into micron-sized segments, and through rapid molecular diffusion and convection mixing, uniform mixing is achieved within milliseconds to obtain the third mixture.

[0097] In step S400, epoxy resin and additives can be added to the third mixture, and then stirred at low speed (300~500r / min) for 10-60min until the epoxy resin and additives are completely dissolved. Next, optional degassing and filtration processes can be performed to obtain the graphene slurry for preparing anti-corrosion coatings according to the present invention.

[0098] According to another embodiment of the present invention, steps S110 and S210 can be performed after steps S100 and S200, respectively. In steps S110 and S210, the third graphene can be added in batches (e.g., 2 to 5 batches), followed by low-speed ultrasound (e.g., power 200W) for 30-60 minutes.

[0099] In this invention, a microchannel mixer is used to mix the ternary system of first graphene, second graphene, and silsesquioxane. Firstly, this facilitates the firm adsorption and intercalation of POSS between almost all graphene sheets, preventing direct contact and π-π stacking between the graphene sheets. More specifically, the instantaneous collision mixing using the microchannel mixer allows the graphene sheets (unmodified and ASG) just dispersed from their respective slurries to encounter POSS molecules in the mixture before they have a chance to re-enter and stack, making it easier for POSS molecules to intercalate between the graphene sheets.

[0100] Furthermore, this invention prevents the imbalance in POSS distribution caused by competitive adsorption by by first mixing the two types of graphene with POSS separately, rather than mixing the dispersions of the first, second, and POSS components separately in a microchannel mixer. Specifically, POSS preferentially accumulates on the surface of ASG. Therefore, if the dispersions of the three components are directly mixed through a microchannel mixer, the distribution of POSS between the two types of graphene will be severely imbalanced, and the unmodified first graphene will agglomerate significantly. Simultaneously, due to the difference in surface charge and polarity between unmodified graphene (hydrophobic, nonpolar groups) and ASG (hydrophilic, negatively charged), when they first meet in the microchannel, if they are not yet fully encapsulated by POSS, they may undergo heterogeneous agglomeration through electrostatic attraction or hydrophobic-hydrophilic interactions. The method of this invention can first protect the graphene with a certain amount of POSS, preventing heterogeneous agglomeration of the unmodified graphene and ASG, which have completely different surface properties, during the simultaneous mixing of the three materials.

[0101] In a preferred embodiment of the present invention, for the mixed system of the present invention, a dual-temperature zone process can be adopted in step S300: the temperature of the first temperature zone is 40-60°C, and the residence time of the mixed liquid is 0.1-3 seconds, which is used to promote the full adsorption and intercalation of POSS on the surfaces of the two graphenes; the temperature of the second temperature zone is 10-25°C, and the residence time of the mixed liquid is 0.1-6 seconds, which is used for rapid cooling to freeze the well dispersed system in the optimal state and prevent irreversible agglomeration or side reactions at high temperatures.

[0102] To provide a clearer understanding of the technical content of this invention, the following embodiments further illustrate the invention. It should be noted that the given embodiments should not be construed as limiting the scope of protection of this invention, nor should comparative examples be necessarily excluded from the scope of protection of this invention. Non-essential improvements and adjustments made to this invention by those skilled in the art based on the content of this invention should still fall within the scope of protection of this invention.

[0103] The above-described technical features of the present invention and the technical features specifically described below (such as in the embodiments) can be combined with each other to form new or preferred technical solutions.

[0104] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the raw materials used in the following examples are all commercially available products that can be purchased from the market or prepared according to the methods of the present invention or existing methods.

[0105] Preparation of second graphene (ASG) In this invention, the second graphene (modified reduced graphene oxide containing amino and sulfonic acid groups, abbreviated as ASG) can be a commercially available product or can be prepared by the following methods. The following preparation methods are merely examples and do not constitute a limitation of this invention. Furthermore, the preparation methods described below are only for illustrating the preparation process of ASG, and the specific amounts of each component are for ease of understanding. The ASG used in the various embodiments below can be prepared according to this method, but its specific amount is not limited to this preparation example.

[0106] Weigh 1g of graphene oxide powder (average lateral size approximately 11μm, average number of layers 3), add 500mL of deionized water, and sonicate (300W power) for 2h to prepare a homogeneous colloidal dispersion of approximately 0.2wt%. Transfer the dispersion to a 1L three-necked flask and place it in an ice-water bath at 0-5℃. Weigh 2.8g of p-aminobenzenesulfonic acid, add 100mL of deionized water and sufficient 37% concentrated hydrochloric acid, and stir until completely dissolved (system pH approximately 1.5); pre-cool the solution to 0℃ and transfer it to a constant pressure dropping funnel for later use. Weigh 1.2g of sodium nitrite and dissolve it in 50mL of ice water, and keep it at 0℃; slowly add it dropwise to the above-mentioned acidic p-aminobenzenesulfonic acid solution, with mechanical stirring throughout the process, for 30min; after the addition is complete, keep it at 0℃ and stir for 1h to generate a diazonium salt solution.

[0107] The prepared diazonium salt solution was slowly added dropwise to the dispersion in an ice-water bath over 2 hours; the temperature was maintained at 0–5°C throughout the process, with continuous mechanical stirring; after the addition was complete, the reaction was maintained in an ice-water bath for 12 hours. After the reaction was complete, the reaction solution was centrifuged (8000 r / min, 10 min), and the supernatant was discarded. Then, the solution was washed three times with deionized water and six times with ethanol by centrifugation until the filtrate was neutral and free of chloride ions. Aminosulfonic acid-modified graphene oxide (SGO) was obtained.

[0108] SGO was redispersed in 500 mL of deionized water and ultrasonically dispersed for 30 min. The dispersion was transferred to a 1 L three-necked flask, and 5 g of L-ascorbic acid was added under stirring to adjust the pH to 9. The mixture was reacted at 90 °C for 6 h. After the reaction was complete, the reaction solution was centrifuged (8000 r / min, 10 min), and the supernatant was discarded. The precipitate was washed three times with deionized water and three times with ethanol until the filtrate was neutral. Finally, it was vacuum dried at 60 °C for 24 h to obtain modified reduced graphene oxide (ASG) containing amino and sulfonic acid groups.

[0109] By adjusting the reaction conditions (such as the amount of p-aminobenzenesulfonic acid added), ASG with different sulfur atom contents and amino contents can be prepared.

[0110] Example 1 Based on a total weight of 1000g, prepare 300g of bisphenol A epoxy resin (E-51 type, Baling Petrochemical), 57g of first graphene (unmodified intrinsic graphene, average lateral dimension 6μm, average number of layers 3, aspect ratio 8), 43g of second graphene (ASG, average lateral dimension 12μm, average number of layers 3, aspect ratio 1.2, prepared according to the method of the above preparation example, wherein the sulfur atom content is 1.9at%, the amino content is 1.4at%, and the C / O atomic ratio is 16), 6g of octaaminoPOSS (Shanghai Keyi Chemical), 20g of additives (including 10g dispersant, 2g defoamer, 4g thixotropic agent, 2g antioxidant, and 2g leveling agent), and the remainder solvent (a mixture of xylene and n-butanol in a volume ratio of 2:1).

[0111] First, 6g of octaaminoPOSS was added to part of the solvent and stirred at 1000 rpm for 30 min. Then, while continuing to stir, 57g of the first graphene was added in three portions (19g / 19g / 19g respectively). After the addition was completed, the stirring speed was increased to 2500 rpm and the mixture was dispersed for 90 min to obtain the first mixture.

[0112] Add 6g of octaaminoPOSS to the remaining solvent and stir at 1000 rpm for 30 min. Then, while continuing to stir, add 43g of second graphene in three portions (14.3g / 14.3g / 14.4g respectively). After the addition is complete, increase the speed to 2500 rpm and disperse for 90 min to obtain the second mixture.

[0113] The first and second mixtures are fed into the two inlets of a microchannel mixer via independent feed lines (the feed flow ratio of the first to the second mixture is 57:43), where they are mixed. The microchannel mixer operates at a pressure of 20 bar, with a first temperature zone of 50°C and a residence time of 0.5 seconds; and a second temperature zone of 15°C and a residence time of 1 second. Within the confined space of the microchannels, the two liquids are separated into micron-sized segments, achieving uniform mixing within milliseconds through rapid molecular diffusion and convection, resulting in the third mixture.

[0114] Finally, 300g of epoxy resin and 20g of additives were added to the third mixture and stirred at 500r / min for 30min to mix thoroughly. After degassing and filtration, the graphene slurry of Example 1 was obtained.

[0115] Example 2 Graphene slurry was prepared using a method essentially the same as in Example 1, except that: based on a total weight of 1000g, the amount of epoxy resin added was adjusted to 100g, the amount of first graphene added was adjusted to 37.5g, the amount of second graphene added was adjusted to 22.5g, the amount of octaaminoPOSS added was adjusted to 3g, and the amount of additives added was adjusted to 10g (the proportions of each component in the additives were the same as in Example 1).

[0116] Example 3 Graphene slurry was prepared using a method essentially the same as in Example 1, except that: based on a total weight of 1000g, the amount of epoxy resin added was adjusted to 500g, the amount of first graphene added was adjusted to 60g, the amount of second graphene added was adjusted to 100g, the amount of octaaminoPOSS added was adjusted to 25g, and the amount of additives added was adjusted to 120g (the proportions of each component in the additives were the same as in Example 1).

[0117] Example 4 Graphene slurry was prepared using a method essentially the same as in Example 1, except that the amount of first graphene added was adjusted to 71.4 g and the amount of second graphene added was adjusted to 28.6 g.

[0118] Example 5 Graphene slurry was prepared using a method essentially the same as in Example 1, except that the amount of first graphene added was adjusted to 52.6 g and the amount of second graphene added was adjusted to 47.4 g.

[0119] Example 6 Graphene slurry was prepared using a method essentially the same as in Example 1, except that the amount of octaaminoPOSS added was adjusted to 6g (i.e., the weight ratio of POSS / graphene = 0.06:1, and the POSS content in this example is 0.6wt%).

[0120] Example 7 Graphene slurry was prepared using a method essentially the same as in Example 1, except that the amount of octaaminoPOSS added was adjusted to 10g (i.e., the weight ratio of POSS / graphene = 0.1:1).

[0121] Example 8 Graphene slurry was prepared using a method essentially the same as in Example 1, except that a first graphene with an average lateral dimension of 4 μm and a second graphene with an average lateral dimension of 9 μm were used.

[0122] Example 9 Graphene slurry was prepared using a method essentially the same as in Example 1, except that a first graphene with an average lateral dimension of 8 μm and a second graphene with an average lateral dimension of 15 μm were used.

[0123] Example 10 Graphene slurry was prepared using a method essentially the same as in Example 1, except that a first graphene and a second graphene with an average of one layer were used.

[0124] Example 11 Graphene slurry was prepared using a method essentially the same as in Example 1, except that a first graphene and a second graphene with an average of 5 layers were used.

[0125] Example 12 Graphene slurry was prepared using a method essentially the same as in Example 1, except that a second graphene with a sulfur atom content of 1.7 at% and an amino atom content of 1.2 at% was used. Specifically, during the preparation of the second graphene, the sulfur atom content was adjusted to 1.7 at% and the amino atom content to 1.2 at% by reducing the amount of p-aminobenzenesulfonic acid added.

[0126] Example 13 Graphene slurry was prepared using a method essentially the same as in Example 1, except that a second graphene with a sulfur atom content of 2.1 at% and an amino atom content of 1.6 at% was used. Specifically, during the preparation of the second graphene, the sulfur atom content was adjusted to 2.1 at% and the amino atom content to 1.6 at% by increasing the amount of p-aminobenzenesulfonic acid added.

[0127] Example 14 The graphene slurry was prepared using a method essentially the same as in Example 1, except that after adding the second graphene and mixing it using a microchannel mixer, 8.6 g of third graphene (hydroxyl-containing reduced graphene oxide with an average lateral size of 8 μm, an average number of layers of 3, and a hydroxyl content of 0.9 at%) was further added.

[0128] Example 15 The graphene slurry was prepared using a method essentially the same as in Example 1, except that after adding the second graphene and mixing it using a microchannel mixer, 21.5 g of third graphene (hydroxyl-containing reduced graphene oxide with an average lateral size of 8 μm, an average number of layers of 3, and a hydroxyl content of 0.9 at%) was further added.

[0129] Example 16 The graphene slurry was prepared using a method essentially the same as in Example 1, except that after adding the second graphene and mixing it using a microchannel mixer, 8.6 g of third graphene (hydroxyl-containing reduced graphene oxide with an average lateral size of 8 μm, an average number of layers of 3, and a hydroxyl content of 0.6 at%) was further added.

[0130] Example 17 The graphene slurry was prepared using a method essentially the same as in Example 1, except that after adding the second graphene and mixing it using a microchannel mixer, 8.6 g of third graphene (hydroxyl-containing reduced graphene oxide with an average lateral size of 8 μm, an average number of layers of 3, and a hydroxyl content of 1.2 at%) was further added.

[0131] Example 18 The graphene slurry was prepared using a method essentially the same as in Example 1, except that: based on a total weight of 1000g, the amount of epoxy resin added was adjusted to 200g, the amount of first graphene added was adjusted to 50g, the amount of second graphene added was adjusted to 30g, the amount of octaaminoPOSS added was adjusted to 3g, and the amount of additives added was adjusted to 10g.

[0132] Example 19 The graphene slurry was prepared using a method essentially the same as in Example 1, except that, based on a total weight of 1000g, the amount of epoxy resin added was adjusted to 400g, the amount of first graphene added was adjusted to 70g, the amount of second graphene added was adjusted to 50g, the amount of octaaminoPOSS added was adjusted to 12g, and the amount of additives added was adjusted to 80g.

[0133] Comparative Example 1 Graphene slurry was prepared using a method essentially the same as in Example 1, except that no second graphene was added, and the amount of first graphene added was adjusted to 100g.

[0134] Comparative Example 2 Graphene slurry was prepared using a method essentially the same as in Example 1, except that the first graphene was not added and the amount of the second graphene added was adjusted to 100g.

[0135] Comparative Example 3 Graphene slurry was prepared using essentially the same method as in Example 1, except that octaaminoPOSS was not added.

[0136] Comparative Example 4 Graphene slurry was prepared using a method essentially the same as in Example 1, except that the amount of octaaminoPOSS added was adjusted to 28g.

[0137] Comparative Example 5 Graphene slurry was prepared using a method essentially the same as in Example 1, except that the second graphene was replaced with an equal amount of amino-modified graphene without sulfonic acid groups (i.e., reduced graphene oxide modified only by ethylenediamine, without sulfonic acid groups).

[0138] Comparative Example 6 Graphene slurry was prepared using essentially the same method as in Example 1, except that octaaminoPOSS was replaced with an equal amount of octaphenylPOSS.

[0139] Comparative Example 7 Graphene slurry was prepared using a method essentially the same as in Example 1, except that the amount of first graphene added was adjusted to 75g and the amount of second graphene added was adjusted to 25g.

[0140] Comparative Example 8 Graphene slurry was prepared using a method essentially the same as in Example 1, except that the amount of first graphene added was adjusted to 48g and the amount of second graphene added was adjusted to 52g.

[0141] Comparative Example 9 Graphene slurry was prepared using a method essentially the same as in Example 1, except that a first graphene with an average lateral dimension of 10 μm and a second graphene with an average lateral dimension of 7 μm were used.

[0142] Comparative Example 10 Graphene slurry was prepared using a method essentially the same as in Example 1, except that second graphene (ASG) with a sulfur atom content of 1.4 at% and an amino atom content of 1.0 at% was used.

[0143] Comparative Example 11 Graphene slurry was prepared using a method essentially the same as in Example 1, except that second graphene (ASG) with a sulfur atom content of 2.3 at% and an amino atom content of 1.8 at% was used.

[0144] Comparative Example 12 Graphene slurry was prepared using a method essentially the same as in Example 1, except that a second graphene with an aspect ratio of 1.8 was used.

[0145] Comparative Example 13 Graphene slurry was prepared using a method essentially the same as in Example 1, except that a first graphene with an aspect ratio of 3 was used.

[0146] Reference Example 1 Graphene slurry was prepared using the exact same formulation as in Example 1, except that: octaaminoPOSS, the first graphene, and the second graphene were simultaneously added to the solvent and dispersed by high-speed stirring at 2500 rpm for 90 min. Then, epoxy resin and additives were added, and the mixture was stirred at 500 rpm for 30 min to achieve homogeneity. That is, this reference example uses a conventional high-speed stirring method instead of a microchannel mixer for mixing.

[0147] See Example 2 The graphene slurry was prepared using the exact same formulation as in Example 1, except that in the step of mixing the first and second mixtures using a microchannel mixer, single-zone temperature control was used instead of dual-zone temperature control, with a temperature of 25°C and a residence time of 1.5 seconds.

[0148] Preparation and spraying of coatings containing graphene slurry The A component of the coating (an epoxy resin + graphene slurry mixture) was prepared using the graphene slurry from the above examples and comparative examples. Component A comprises: 25 wt% bisphenol A epoxy resin, 15 wt% graphene slurry, 10 wt% titanium dioxide (D50 6 μm), 10 wt% iron phosphate powder (D50 6 μm), 10 wt% talc powder (D50 6 μm), 3 wt% additives (including 1.5 wt% anti-settling agent, 1 wt% dispersant, and 0.5 wt% defoamer), and 27 wt% solvent (a xylene / n-butanol mixed solvent with a volume ratio of 7:3). The method for preparing component A follows conventional methods in the art, and its detailed description is omitted here.

[0149] Then, component A and component B (90wt% of type 650 polyamide curing agent (amine value approximately 300 mg KOH / g) and 10wt% of solvent (xylene / n-butanol mixed solvent at a volume ratio of 7:3)) were mixed at a volume ratio of 4:1. After curing, the mixture was sprayed onto the surface of Sa2.5 grade steel, with a dry film thickness of approximately 100 μm, and left to stand at room temperature for 7 days. Other application details were performed according to conventional techniques in the field and are not described in detail here.

[0150] Evaluation 1: Storage stability of slurry Referring to GB / T6753.3-1986, the graphene slurries of each example and comparative example were sealed and stored at standard temperatures (23±2℃ or 25±1℃) for 6 months. Their storage stability was evaluated by visual observation and viscosity change rate. The evaluation criteria were divided into three levels: Advantages: No stratification, no sedimentation, no skin formation; viscosity change rate ≤5%; Good: Slight stratification or a small amount of soft sediment, which can be restored to homogeneity after stirring; viscosity change rate ≤15%; Poor: Severe stratification, hard sedimentation or gelation that cannot be recovered by stirring, viscosity change rate >15%.

[0151] Evaluation 2: Scraper fineness Referring to GB / T1724-2019, the fineness of the graphene slurries in the examples and comparative examples was determined using a scraper fineness meter with a diameter of 0-100 μm to indicate the degree of dispersion of graphene and other solid particles therein. The smaller the value, the better the dispersibility.

[0152] Evaluation 3: Coating resistivity To evaluate the formation efficiency of the graphene conductive network in the coating, the coatings from the examples and comparative examples were sprayed onto an insulating glass plate to prepare a coating with a dry film thickness of 100 μm. Five points were randomly selected on the film surface for measurement, and the average value was taken. The lower the resistivity value, the more complete the conductive network within the coating.

[0153] Evaluation 4: Coating Adhesion In accordance with GB / T5210-2006, the coating surfaces (dry film thickness 100 μm) of the examples and comparative examples were tested using an adhesion tester (PosiTest AT-M). The test results are expressed as pull-off adhesion values ​​(MPa), with higher values ​​indicating stronger adhesion between the coating and the substrate.

[0154] Evaluation 5: Salt spray resistance Referring to GB / T10125-2021, an X-shaped scratch was made in the center of the paint film of the coated steel plate in the examples and comparative examples, extending to the substrate; a 5% NaCl solution was continuously sprayed, and the width of the erosion on one side of the scratch (mm) and the time for blistering / rusting / peeling of the paint film (h) were recorded; the smaller the erosion width and the longer the failure time, the better the anti-corrosion performance.

[0155] Evaluation 6: Electrochemical Impedance Spectroscopy (EIS) After immersion in 3.5 wt% NaCl solution for 720 h, the low-frequency impedance modulus (|Z|) of the coating was tested. 0.01 (Hz). The higher the impedance modulus, the better the coating's impermeability and corrosion resistance.

[0156] The evaluation results are shown in Table 1.

[0157] Table 1

[0158]

[0159] As shown in Table 1, at least the following conclusions can be drawn: Comparing Example 1 with Comparative Examples 1-3, it can be seen that Example 1 is significantly better than Comparative Examples 1-3 in all evaluation indicators, which fully demonstrates that the ternary combination system of the first graphene, the second graphene and the octaamino POSS of the present invention can achieve a significant synergistic effect. All three are indispensable and together achieve synergistic protection of physical shielding, chemical passivation and cross-linking enhancement.

[0160] The comparison between Example 1 and Comparative Example 5 verifies the crucial role of the sulfonic acid group in ASG. The scraper fineness of Comparative Example 5 (using ordinary amino-modified graphene without sulfonic acid groups instead of ASG) was 26 μm, significantly inferior to the 13 μm of Example 1, and its storage stability decreased to "good". This indicates that without the physical steric hindrance provided by the sulfonic acid group and its effect on regulating the surface polarity of the sheets, the dispersion stability of ordinary amino-modified graphene in the non-aqueous organic solvent system of this invention is significantly reduced, making it unable to form a uniform mixture with unmodified graphene and POSS. Other properties of Comparative Example 5 are also inferior to those of Example 1. This comparison demonstrates the irreplaceable role of the sulfonic acid group in achieving long-term dispersion stability in the slurry system of this invention. While amino modification alone can provide some interfacial reactivity, it cannot solve the fundamental dispersion problem of graphene in this organic solvent system.

[0161] The unique advantages of octaaminoPOSS can be verified by comparing Example 1 and Comparative Example 6. Comparative Example 6 (using octaphenylPOSS instead of octaaminoPOSS) had a scraper fineness of 16 μm and excellent storage stability, indicating that octaphenylPOSS can effectively intercalate and disperse graphene through π-π stacking. However, its resistivity, adhesion, salt spray corrosion resistance, and impedance were all inferior to those of Example 1. This indicates that although both octaphenylPOSS and octaaminoPOSS can achieve intercalation and dispersion of graphene through steric hindrance, the eight active amino groups on the periphery of octaaminoPOSS can deeply participate in the curing and crosslinking reaction of epoxy resin, chemically anchoring the graphene sheets within the resin network, thereby significantly improving interfacial bonding and coating density. In contrast, octaphenylPOSS, lacking reactive functional groups, can only provide physical dispersion and cannot achieve chemical crosslinking enhancement; its anti-corrosion performance is far inferior to that of octaaminoPOSS.

[0162] Comparing Examples 4-5 with Comparative Examples 7-8, it can be seen that: by mixing the first graphene and the second graphene in the preferred proportions according to the present invention, good performance of the coating can be achieved.

[0163] Comparing Examples 6-7 with Comparative Example 4, it can be seen that when the amount of octaaminoPOSS added is within the preferred range of this invention, good coating performance can be achieved. Specifically, the amount of POSS added in Comparative Example 4 was 2.8 wt%. Although its storage stability was "excellent" and the scraper fineness was only 15 μm, its resistivity significantly increased to 1.52 Ω·cm, salt spray corrosion spread increased to 1.9 mm, and impedance decreased to 4.2 × 10⁻⁶. 9 Ω·cm². This indicates that while excessive POSS is beneficial for dispersion, its insulating siloxane framework affects the conductive pathways between graphene sheets, leading to a significant increase in coating resistivity and a marked decrease in corrosion resistance.

[0164] Comparing Examples 8-9 with Comparative Example 9, it can be seen that when the sizes of the first and second graphenes are within the preferred range of the present invention, good coating performance can be achieved. Specifically, when the sizes of the first and second graphenes do not meet the limited range of the present invention, the large-sized unmodified graphene cannot be effectively filled by the small-sized ASG, forming a large number of interconnected micropores. Corrosive media can quickly penetrate along these pores, severely weakening the shielding effect of the coating. At the same time, the smaller ASG cannot provide sufficient long-range framework function, and the continuity of the conductive network is also affected.

[0165] Comparing Examples 12-13 with Comparative Examples 10-11, it can be seen that when the content of sulfonic acid groups and amino groups in the second graphene is within the preferred range of the present invention, good coating performance can be achieved. Specifically, when the grafting density of sulfonic acid groups and amino groups is insufficient, as in Comparative Example 10, the physical steric hindrance effect between ASG sheets is insufficient, making it difficult to effectively suppress π-π stacking and agglomeration between sheets, and the slurry is prone to stratification or sedimentation; at the same time, insufficient amino content leads to insufficient passivation effect on metals, and limited improvement in interfacial bonding. When sulfonic acid groups and amino groups are excessive, as in Comparative Example 11, the excessive sulfonic acid groups form a dense polar layer on the surface of ASG sheets, increasing the moisture absorption tendency and permeability of the coating after curing, which has an adverse effect on long-term water resistance; excessive amino groups may react with CO2 in the air to form carbamates during slurry storage, affecting the long-term stability of the slurry.

[0166] Comparing Comparative Examples 12-13 with Example 1, it can be seen that when the aspect ratios of the first and second graphenes are within the preferred range of this invention, good coating performance can be achieved. Specifically, in Comparative Example 12, the aspect ratio of the second graphene is too large, and its shape is closer to a strip than a circle / square, making it difficult to achieve optimal in-plane orientation and spreading in the coating, resulting in a decrease in shielding effect. In Comparative Example 13, the aspect ratio of the first graphene is too small, and its shape is close to a circle, making it difficult to construct a continuous long-range conductive network, increasing tunneling resistance, and significantly increasing the sheet resistance of the coating.

[0167] Comparing Examples 14-17 with Example 1, it can be seen that when a third graphene is further added, better coating performance can be achieved.

[0168] Comparing Reference Example 1 with Example 1, it can be seen that when a microchannel mixer is used to prepare graphene slurry, better coating performance can be achieved.

[0169] Comparing Reference Example 1 and Reference Example 2, it can be seen that better coating performance can be achieved when dual-zone temperature control is used during mixing using a microchannel mixer.

[0170] The conclusions described above are only a part of the beneficial effects that can be achieved based on the inventive concept and the technical solution of the present invention. Other beneficial effects not mentioned can be derived from the results in Table 1.

[0171] In summary, this invention achieves multiple synergistic protections through a ternary synergistic compounding of unmodified graphene, aminosulfonic acid-modified graphene (ASG), and octaaminocage-type polysilsesquioxane, combined with a preparation process of premixing each component separately and then uniformly mixing them in a microchannel reactor. The sulfonic acid groups of ASG provide electrostatic dispersion stability, while the amino groups achieve metal passivation and resin anchoring. Unmodified graphene compensates for conductivity and forms a size-graded filler with ASG, constructing a continuous conductive network and physical shielding layer. The octaaminocage-type POSS provides steric hindrance to prevent agglomeration, and its multiple active amino groups participate in resin curing to form an interpenetrating network, chemically anchoring the graphene in the coating. The synergistic effect of these three components results in ultra-long storage stability of the slurry and low resistivity, high adhesion, excellent salt spray resistance, and high impedance performance of the coating.

[0172] Finally, it should be emphasized that the above are merely preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention can have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A graphene slurry for use in anti-corrosion coatings, characterized in that, Based on the total weight of the graphene slurry, the graphene slurry comprises: 10wt% to 50wt% epoxy resin; 6 wt% to 16 wt% of graphene; 0.3wt% to 2.5wt% of sesquioxane; 1 wt% to 12 wt% of adjuvants; and The remaining solvent, The graphene comprises a first graphene and a second graphene, wherein the first graphene is unmodified graphene, the second graphene is graphene containing amino and sulfonic acid groups, and the silsesquioxane comprises octaaminocage-type polysilsesquioxane.

2. The graphene slurry according to claim 1, characterized in that, The second graphene is 2,5-diaminobenzenesulfonic acid-modified reduced graphene oxide.

3. The graphene slurry according to claim 1, characterized in that, The average lateral dimension of the second graphene is larger than that of the first graphene. The average number of layers in the second graphene is less than or equal to the average number of layers in the first graphene. In the graphene slurry, the content of the second graphene is less than the content of the first graphene. In the graphene slurry, the content of the silsesquioxane is less than the content of the second graphene.

4. The graphene slurry according to claim 1, characterized in that, In the graphene slurry, the weight ratio of the second graphene to the first graphene is 0.4:1 to 0.9:1, and the weight ratio of the silsesquioxane to the graphene is 0.05:1 to 0.1:

1.

5. The graphene slurry according to claim 1, characterized in that, The average lateral dimension of the second graphene is 9 μm to 15 μm. The average lateral dimension of the first graphene is 4 μm to 8 μm. The second graphene has an average of 1 to 5 layers. The first graphene has an average number of layers of 1 to 5.

6. The graphene slurry according to claim 1, characterized in that, The sulfur atom content in the second graphene is 1.7 at% to 2.1 at%. The C / O atomic ratio in the second graphene is greater than or equal to 15. The amino content in the second graphene is 1.2 at% to 1.6 at%.

7. The graphene slurry according to claim 1, characterized in that, The graphene also includes a third graphene, which is a hydroxyl-containing graphene. The average lateral dimension of the third graphene is greater than that of the first graphene and smaller than that of the second graphene. In the graphene slurry, the content ratio of the third graphene to the second graphene is 0.2:1 to 0.5:

1.

8. The graphene slurry according to claim 7, characterized in that, The hydroxyl content in the third graphene is from 0.6 at% to 1.2 at%.

9. The graphene slurry according to claim 1, characterized in that, Based on the total weight of the graphene slurry, the graphene slurry comprises: 20wt% to 40wt% epoxy resin; 8 wt% to 14 wt% of graphene; 0.3wt% to 1.5wt% of sesquioxane; 1 wt% to 8 wt% of adjuvants; and The remaining solvent, The solvent includes one or more of xylene, n-butanol, toluene, ethylbenzene, N-methylpyrrolidone, N,N-dimethylformamide, acetone, tetrahydrofuran, ethanol, water, and ethyl acetate. The additives include one or more of defoamers and dispersants.

10. A method for preparing a graphene slurry for anti-corrosion coatings according to any one of claims 1 to 9, characterized in that, The method includes the following steps: Silsesquioxane and the first graphene were added to a solvent to obtain a first mixture; Silsesquioxane and second graphene are added to a solvent to obtain a second mixture; The first and second mixtures are mixed using a microchannel mixer to obtain a third mixture; as well as Epoxy resin and additives are added to the third mixture.